Dietary alpha‐linolenic acid reduces platelet activation and collagen‐mediated cell adhesion in sickle cell disease mice. (1st December 2021) - Stivala, Simona; Gobbato, Sara; Bonetti, Nicole; Camici, Giovanni G.; Lüscher, Thomas F.; Beer, Jürg H.
Abstract: Background: Sickle cell disease (SCD) is a genetic hemoglobinopathy associated with high morbidity and mortality. The primary cause of hospitalization in SCD is vaso‐occlusive crisis (VOC), mediated by alteration of red blood cells, platelets, immune cells and a pro‐adhesive endothelium. Objectives: We investigated the potential therapeutic use of the plant‐derived omega‐3 alpha‐linolenic acid (ALA) in SCD. Methods: Berkeley mice were fed a low‐ or high‐ALA diet for 4 weeks, followed by analysis of liver fibrosis, endothelial activation, platelet activation and formation of platelet‐neutrophils aggregates. Aggregation of platelets over collagen under flow after high‐ALA was compared to a blocking P‐selectin Fab. Results: Dietary high‐ALA was able to reduce the number of sickle cells in blood smear, liver fibrosis, and the expression of adhesion molecules on the endothelium of aorta, lungs, liver and kidneys (VCAM‐1, ICAM‐1 and vWF). Specific parameters of platelet activation were blunted after high‐ALA feeding, notably P‐selectin exposure and the formation of neutrophil‐platelet aggregates, along with a correspondingly reduced expression of PSGL‐1 on neutrophils. By comparison, in vivo treatment of SCD mice with the anti‐P‐selectin Fab was able to similarly reduce the formation of neutrophil‐platelet aggregates, but did not reduce GpIbα shedding nor the activation of the αIIb β3 integrin in response to thrombin. Both ALA feeding and P‐selectin blocking significantly reduced collagen‐mediated cell adhesion under flow. Conclusions: Dietary ALA is able to reduce the pro‐inflammatory and pro‐thrombotic state occurring in the SCD mouse model and may represent a novel, inexpensive and readily available therapeutic strategy for SCD.